Analysis of The Policy of Granting Concession Rights to Port Business Entities in The Framework of Acceleration of Port Development in Indonesia - Budiarto Santoso; Datep Purwa Saputra; Librita Arifiani (Dinasti Review, 2026)
Ports are essential infrastructure that support regional connectivity and national economic growth. However, Indonesia’s limited fiscal capacity constrains port development. To overcome this, the government has introduced a concession policy granting operational rights to Port Business Entities (BUP) through public–private cooperation. This study analyzes the effectiveness of the concession policy in accelerating port development using a qualitative descriptive–analytical approach. Data were collected through literature reviews, document analysis, and interviews with port sector stakeholders, analyzed using the Miles and Huberman model and the Logical Framework Approach (LFA). The results show that the policy has been implemented but faces challenges in policy planning, supervision, and risk allocation. Improving transparency, accountability, and legal certainty is necessary. This study recommends strengthening regulations, oversight institutions, and fair concession models, offering novelty through an integrated analysis and a performance-based concession framework for accelerating port development in Indonesia.